Faktor-Faktor yang Mempengaruhi Pengeluaran Makanan Pendidikan dan Kesehatan pada Rumah Tangga Indonesia - Farrel, Muhammad; Marta, Joan; Sentosa, Sri Ulfa (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
The purpose of this study was to analyze the effect of education of the head of household, gender, occupation of the head of household, employment status, how much education the mother has, number of family members, region on food, education and health expenditure in Indonesia. The type of research conducted is descriptive and inductive. Using the Tobit regression model. This research was conducted in Indonesia, using Susenas Indonesia data in 2020. Data collection used documentation techniques and literature studies. Data were analyzed using descriptive analysis, inductive analysis, hypothesis testing. The results of the study were Education of the head of household (Edu), gender of the head of household (Gender), sector of employment of the head of household (Empstat), sector of employment of the mother, Education of the mother, number of family members (Hhsz), and regional variables have a positive and significant relationship to Food, Education and Health Expenditure in Households.